2014
DOI: 10.1155/2014/872320
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Pattern of Herb and Supplement Use in the United States: Results from the 2002, 2007, and 2012 National Health Interview Surveys

Abstract: Background. In 1990s, complementary and alternative medicine (CAM), including use of herbs and supplements, gained popularity in the United States. However, more recent surveys suggest that demand for herbs and supplements has stabilized. Objective. This study examined the prevalence, patterns, and changes in herb and supplement use among the US adults, using the 2002, 2007, and 2012 National Health Interview Surveys (NHIS). Methods. Weighted population estimates were derived from three complementary and alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 18 publications
1
52
2
1
Order By: Relevance
“…Non-vitamin, non-mineral natural product (NVNM) dietary supplements (DS), the most popular complementary medicine modality in the USA, are used by almost 20% of US adults 1. Of these, turmeric ( Curcuma longa L) is one of the top selling DS, with exponentially increasing sales reaching US$69 million in 2016 2.…”
Section: Introductionmentioning
confidence: 99%
“…Non-vitamin, non-mineral natural product (NVNM) dietary supplements (DS), the most popular complementary medicine modality in the USA, are used by almost 20% of US adults 1. Of these, turmeric ( Curcuma longa L) is one of the top selling DS, with exponentially increasing sales reaching US$69 million in 2016 2.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of herbals in females may be most common in the population. Such observation is often made in CAM/herbal use prevalence studies [1][2][3]. It is therefore expected that this population is also overrepresented in all included reports.…”
Section: Suspect Herbalsmentioning
confidence: 94%
“…There is an increased prevalence in use of herbal medicines among the adult population in many western countries [1][2][3]. The most recent 2012 US National Health Interview Survey showed that 18% of adults used natural products including herbal medicine during the past 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, the NHIS reported that 53.6 million Americans utilized herbal remedies and dietary supplements. 1 The sale of botanical dietary supplements was estimated at $11.5 billion in 2012. 2 A population-based survey of 2,982 respondents conducted by Emory University in 2004 indicated that while 20% of the population used medicinal herbs, over 33% admitted to daily use.…”
Section: Introductionmentioning
confidence: 99%